Fault Detection from Images of Railroad Lines Using the Deep Learning Model Built with the Tensorflow Library - Şener, Abdullah; Ergen, Burhan; Toğaçar, Mesut (My University, 2022)
A means of transportation is the way in which an object, person, or service is transported from one place to another. Rail transportation occupies an important place in terms of cost and reliability. Most train accidents are caused by faults in railroad tracks. Detecting faults in railroad tracks is a difficult and time-consuming process compared to conventional methods. In this study, an artificial intelligence based model is proposed that can detect faults in railroad tracks. The dataset used in the study consists of defective and non-defective railroad images. The proposed model consists of foldable neural networks developed using the Tensorflow library. Softmax method was used as a classifier. An overall accuracy of 92.21% was achieved in the experiment.
Keywords: Deep learning; Artificial intelligence; Decision support systems; Rail fault detection